Impact of Transposable Elements on Methylation and Gene Expression across Natural Accessions of Brachypodium distachyon. (27th August 2020) - Wyler, Michele; Stritt, Christoph; Walser, Jean-Claude; Baroux, Célia; Roulin, Anne C
Abstract: Transposable elements (TEs) constitute a large fraction of plant genomes and are mostly present in a transcriptionally silent state through repressive epigenetic modifications, such as DNA methylation. TE silencing is believed to influence the regulation of adjacent genes, possibly as DNA methylation spreads away from the TE. Whether this is a general principle or a context-dependent phenomenon is still under debate, pressing for studying the relationship between TEs, DNA methylation, and nearby gene expression in additional plant species. Here, we used the grass Brachypodium distachyon as a model and produced DNA methylation and transcriptome profiles for 11 natural accessions. In contrast to what is observed in Arabidopsis thaliana, we found that TEs have a limited impact on methylation spreading and that only few TE families are associated with a low expression of their adjacent genes. Interestingly, we found that a subset of TE insertion polymorphisms is associated with differential gene expression across accessions. Thus, although not having a global impact on gene expression, distinct TE insertions may contribute to specific gene expression patterns in B. distachyon.